A critical eye at the application of the prior consultation in Peru to the purpose of the 30th anniversary of the 169 Convention of the International Labor Organization - Rebaza Vílchez, Karen Maribel (2019)
June 27 marks the thirtieth anniversary since the General Conference of the International Labor Organization (ILO) adopted the "Convention 169 on Indigenous and Tribal Peoples in Independent Countries." This multilateral treaty, of which Peru has been a party since 1994, brought with it the state responsibility to adopt specific laws, policies and programs focused on the rights and welfare of indigenous and tribal peoples. Among the scope of the Convention, is the recognition of the right to prior consultation, in this sense, this article provides a critical reflection on its application in Peru.